2017
DOI: 10.1080/1057610x.2017.1352280
|View full text |Cite
|
Sign up to set email alerts
|

Online as the New Frontline: Affect, Gender, and ISIS-Take-Down on Social Media

Abstract: Using a dataset of more than 80 accounts during 2015, this article explores the gendered ways in which self-proclaiming Twitter Islamic State of Iraq and Syria (ISIS) supporters construct community around "suspension." The article argues that suspension is an integral event in the online lives of ISIS supporters, which is reproduced in online identities. The highly gendered roles of ISIS males and females frame responses to suspension, enforcing norms that benefit the group: the shaming of men into battle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
(19 reference statements)
0
17
0
1
Order By: Relevance
“…11 This does not mean they do not promote violence, however, often shaming men into action. 12 Similarly, those working on women's roles in the far right, have outlined the possibilities for women joining white supremacist, Nazi and radical right groupsdespite the homosociality of such groups -and their findings mirror those above. While fewer in number, and often without leadership powers, many far right women embrace roles of domesticity, what Hardisty termed "kitchen sink activism."…”
Section: Part I: Extremism and Gender: A Fundamental Relationship?mentioning
confidence: 88%
“…11 This does not mean they do not promote violence, however, often shaming men into action. 12 Similarly, those working on women's roles in the far right, have outlined the possibilities for women joining white supremacist, Nazi and radical right groupsdespite the homosociality of such groups -and their findings mirror those above. While fewer in number, and often without leadership powers, many far right women embrace roles of domesticity, what Hardisty termed "kitchen sink activism."…”
Section: Part I: Extremism and Gender: A Fundamental Relationship?mentioning
confidence: 88%
“…First, disruption on Twitter has led to the migration of pro‐ISIS activity to encrypted messaging applications such as Telegram (Prucha, 2016). Second, having faced suspension on Twitter and other social media platforms can be a badge of pride for extremists, and plays a role in community‐building among these networks (Pearson, 2018).…”
Section: Content Moderation and Takedownmentioning
confidence: 99%
“…This is particularly important in the current context, given that claims of anti-Muslim prejudice are utilised by jihadist radicalisers who deploy an us vs. them discourse to Other the West (Lorenzo-Dus and Macdonald, 2018). Indeed, a study of IS Twitter activity found that suspension played an important role in community-building, with the majority of the accounts studied referring to Twitter's use of suspension as a specific tool to persecute Muslims (Pearson, 2017). Examples included the tweets ‘There has been a major Twitter purge targeting Muslims’ and ‘I got #Radicalised when me and my people started to get suspended on every social media platform’.…”
Section: Prior Restraint and Technological Due Processmentioning
confidence: 99%